Bioactive constituents of Lindernia crustacea and its anti-EBV effect via Rta expression inhibition in the viral lytic cycle. (25th March 2020) - Tsai, Yu-Chi; Hohmann, Judit; El-Shazly, Mohamed; Chang, Li-Kwan; Dankó, Balázs; Kúsz, Norbert; Hsieh, Chi-Ting; Hunyadi, Attila; Chang, Fang-Rong
Abstract: Ethnopharmacological relevance: Lindernia crustacea (L.) F.Muell. (Scrophulariaceae) was selected for phytochemical investigation owing to its traditional use against human herpes virus infection and its anti-Epstein–Barr virus (EBV) effect. Aims of the study: The present study focused on the phytochemical investigation of L. crustacea including the isolation and structure determination of its biologically active compounds. Compounds with anti-EBV effects were also investigated. Materials and methods: The EtOH extract of L. crustacea was subsequently partitioned using different solvents. The EtOAc fraction was subjected to several chromatographic methods to obtain pure compounds. The structures of all isolates were established by spectroscopic analysis and compared with previously reported physical data. The anti-EBV effect was evaluated in an EBV-containing Burkitt's lymphoma cell line (P3HR1) to study the expression of EBV lytic proteins. Results: Thirty-three compounds, including one diterpene (1 ), four anthraquinones (2 –5 ), two ionones (6 and 7 ), fourteen phenylpropanoid glycosides (8 –21 ), five flavonoids (22 –26 ), one lignan glycoside (27 ), one phenethyl alcohol glycoside (28 ), one phenylpropene glycoside (29 ), one glucosyl glycerol derivative (30 ), one furanone (31 ), and two cinnamic acid derivatives (32 and 33 ), were isolated from the ethanolic extract of the plant. All isolated compounds were obtained for the first time from Lindernia sp. The evaluation of the anti-EBV activity of L. crustacea crude extract, partitioned fractions, and constituents was performed for the first time. Phytol (1 ), aloe-emodin (2 ), byzantionoside B (7 ), a mixture of trans -martynoside (8 ) and cis -martynoside (9 ), a mixture of trans -isomartynoside (10 ) and cis -isomartynoside (11 ), luteolin-7- O - β -D-glucopyranoside (24 ), and apigenin-7- O -[ β -D-apiofuranosyl (1→6)- β -D-glucopyranoside] (25 ) exhibited significant inhibitory effects on the EBV lytic cycle at 20 μg/mL in the immunoblot analysis. On the other hand, (6 R, 7 E, 9 R )-3-oxo- α -ionol- β -D-glucopyranoside (6 ) and a mixture of trans -dolichandroside A (12 ) and cis -dolichandroside A (13 ) showed moderate anti-EBV activity at 20 μg/mL. Conclusions: L. crustacea and its active isolates could be developed as potential candidates against EBV. Our findings provide scientific evidence for the traditional use of L. crustacea for its antiviral effects. Graphical abstract: Image 1